Tuning cellular responses to BMP-2 with material surfaces. (February 2016) - Migliorini, Elisa; Valat, Anne; Picart, Catherine; Cavalcanti-Adam, Elisabetta Ada
Graphical abstract: Highlights: New material surfaces are tailored to provide physical and chemical cues that regulate BMP-2 activity. Physical entrapment or chemical binding of BMP-2 on material surfaces modulate the temporal activity of BMP-2. Surface patterning at different length scales allows the spatial control of BMP-2. Material surfaces copresenting BMP-2 together with extracellular matrix components are suitable platforms to study cells adhesion and response to external stimuli. ABSTRACT: Bone morphogenetic protein 2 (BMP-2) has been known for decades as a strong osteoinductive factor and for clinical applications is combined solely with collagen as carrier material. The growing concerns regarding side effects and the importance of BMP-2 in several developmental and physiological processes have raised the need to improve the design of materials by controlling BMP-2 presentation. Inspired by the natural cell environment, new material surfaces have been engineered and tailored to provide both physical and chemical cues that regulate BMP-2 activity. Here we describe surfaces designed to present BMP-2 to cells in a spatially and temporally controlled manner. This is achieved by trapping BMP-2 using physicochemical interactions, either covalently grafted or combined with other extracellular matrix components. In the near future, we anticipate that material science and biology will integrate and further develop tools for in vitro studies and potentially bring some of them toward in vivo applications.